Pattern of Symptoms, Aetiologies, and Associated Risk Factors of Unilateral Acute Non-granulomatous Anterior Uveitis Cases Presenting in a Tertiary Eye Institute of Nepal - Manandhar, Anu; Gupta, Vidisha; Pandey, Araniko (Nepalese Journal of Ophthalmology, 2024)
Introduction: Unilateral cases of acute non-granulomatous anterior uveitis (ANGAU) make major portion in anterior uveitis group. It is characterised by recurrent episodes of sudden onset of redness, pain, and photophobia in one eye. It comprises of acute anterior uveitis mainly due to seronegative spondyloarthopathies and some idiopathic. Objective: To know the pattern of symptoms of ANGAU in detail, to analyse if smoking and stress could be its risk factors, to confirm its association with human leukocyte antigen (HLA)-B27 gene, and to find out the effect of season in its relapse in Nepali patients. Methodology: In this hospital-based observational study done from 2017 November to 2019 February at Tilganga Institute of Ophthalmology, all cases (census) of ANGAU were included after ethical approval. Result: Of the total 70 patients, 38 (54.3%) were male and 32 (45.7%) were female. Majority of patients were between ages of 31-40 years (32.9%) with range (mean±SD) of 18-74 (40.16±13.96) years. Redness (91.4%), pain (64.3%), photophobia (64.3%), decreased vision (61.4%), and watering (20%) were major symptoms. Most presented during summer (45.7%). Majority were either smoker at present (40%) or were smokers in the past (24.3%). There was a positive history of stress factor in 24.3% patients. Of 50/70 cases who underwent HLA-B27 testing, 30 (60%) were positive. Sixteen out of 70 patients (22.8%) had features suggestive of SpA. Twelve out of 16 SpA cases (17.1%) had a positive HLA-B27 report. But, four patients (5.7%) denied an HLA-B27 testing. Conclusion: Unilateral NGAU in Nepali population is strongly associated with present or past smoking, not strongly associated with stress factor, relapses mostly in summer season, and shows HLA-B27 gene positivity in slightly >50% population. Other than pain, redness, photophobia, and decreased vision, watering can also be one of the presenting symptoms of NGAU cases.